Surface defection reduces cytotoxicity of Zn(2-methylimidazole)2 (ZIF-8) without compromising its drug delivery capacity. Issue 5 (7th January 2016) - Shearier, Emily; Cheng, Peifu; Zhu, Zhuan; Bao, Jiming; Hu, Yun Hang; Zhao, Feng
Abstract : Surface defection incurs bond breakage and unsaturated Zn-sites and N-sites on the external surface of ZIF-8 particles. These bonds in turn bind H2 O molecules in an aqueous environment, converting ZIF-8 from hydrophobic to hydrophilic. Abstract : Zn(2-methylimidazole)2 (ZIF-8), as one of the most important metal–organic framework (MOF) molecules, is a promising candidate for drug delivery due to its low-density structure, high surface area, and tunable frameworks. However, ZIF-8 exhibits a high cytotoxicity associated with its external hydrophobic surface, which significantly restricts its application in drug delivery and other biomedical applications. Commonly used chemical functionalization methods would convert the hydrophobic surface of ZIF-8 to hydrophilic, but the generated functional groups on its internal surface may reduce its pore sizes or even block its pores. Herein, a surface defection strategy was applied on the external surface of ZIF-8 to enhance its hydrophilicity without reducing or blocking the internal pores. In this approach, mechanical ball-milling was used to incur defects on the external surface of ZIF-8, leading to unsaturated Zn-sites and N-sites which subsequently bound H2 O molecules in an aqueous environment. Furthermore, hydroxyurea delivery and cell cytotoxicity of ZIF-8 with and without the external surface treatment were evaluated. It was found that 5 min ball milling changed the hydrophobic–hydrophilic balance of ZIF-8, resulting in significantly higher cell viability without compromising its hydroxyurea loading and release capacity. Such a simple mechanical ball-milling followed by water-treatment provides a general technique for surface-modification of other MOF molecules, which will undoubtedly magnify their biomedical applications.